Synthesis of flower-like TiO2 microsphere/graphene composite for removal of organic dye from water. (5th June 2016) - Wang, Yawen; Mo, Zunli; Zhang, Ping; Zhang, Chun; Han, Lijuan; Guo, Ruibin; Gou, Hao; Wei, Xiaojiao; Hu, Rere
Abstract: A surfactant-assisted hydrothermal route was developed for the synthesis of three-dimensional (3D) flower-like TiO2 microsphere decorated graphene composite (FT/GN) based on the hydrothermal reduction of graphene oxide and formation of TiO2 microsphere in the presence of poly(vinyl pyrrolidone) (PVP). By several characterization methods such as X-ray diffraction, scanning electron microscopy, transmission electron microscopy and X-ray photoelectron spectroscopy, we demonstrated that uniform flower-like TiO2 (FT) microsphere with average diameter of 1.4 μm have successfully anchored on the surface of graphene sheets. Effects of PVP and reaction temperature on the microstructure of the composite were investigated. Benefits from the combined graphene with FT microsphere were that the FT/GN composite exhibited higher adsorption capacity and photocatalytic activity for the removal of rhodamin B (RhB) than blank FT microsphere and P25. Especially, the removal rate of RhB using FT/8GN composite under UV light irradiation reached 99.2% in 80 min, with corresponding TOC removal efficiency of 66.49%. Moreover, the recycled photoactivity tests showed that the prepared composite were stable enough and maintained high removal efficiency for RhB even after four cycles. It is expected that the present synthetic strategy may provide a new strategy for the fabrication of various GN-based hybrids with multi-dimensional structure. Graphical abstract: Highlights: Flower-like TiO2 microsphere decorated graphene composite were fabricated by one-step hydrothermal process. Effects of poly(vinyl pyrrolidone) and reaction temperature on the microstructure of Flower-like TiO2 microsphere decorated graphene composite were investigated. The flower-like TiO2 microsphere/graphene composite exhibited better adsorption capacity and photocatalytic activity for the removal of rhodamin B than pure TiO2 microsphere and P25.